Pengaruh Fee Audit, Audit Tenure, Dan Kompleksitas Perusahaan Terhadap Audit Report Lag - Hana Afifatu Daniyah; Fina Fitriyana (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study analyzes the effect of audit fees, audit tenure, and company complexity on audit report lag in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Audit report lag is the interval between a company's fiscal year-end date and the date its independent auditor's report is issued. This study uses a quantitative associative approach with secondary data from companies' annual reports. Using purposive sampling, 16 companies were selected, yielding 80 firm-year observations, analyzed with panel data regression using EViews 12. Results show that, simultaneously, audit fees, audit tenure, and company complexity affect audit report lag. Partially, audit fees have no significant effect, while audit tenure and company complexity each have a significant effect on audit report lag. These findings indicate that a longer auditor-client relationship and a more complex company structure influence the length of the audit completion process.